Associations of long-term exposure to ambient PM2.5 with mortality in Chinese adults: A pooled analysis of cohorts in the China-PAR project - Yang, Xueli; Liang, Fengchao; Li, Jianxin; Chen, Jichun; Liu, Fangchao; Huang, Keyong; Cao, Jie; Chen, Shufeng; Xiao, Qingyang; Liu, Xiaoqing; Shen, Chong; Yu, Ling; et al. (Environment international, 2020)
•Combining satellite-based PM2.5 levels with cohort data in general Chinese adults.•A broad range of long-term exposure to PM2.5 from 31 μg/m3 to 97 μg/m3.•A weak exponential curve observed between long-term PM2.5 exposure and mortality. The concentration-response relationship between mortality and long-term exposure to fine particulate matter (PM2.5) has not been fully elucidated, especially at high levels of PM2.5 concentrations. We aimed to evaluate chronic effects of ambient PM2.5 exposure on deaths among Chinese adults in high-exposure settings. Participants of the Prediction for Atherosclerotic cardiovascular disease Risk in China (China-PAR) project were included from four prospective cohorts among Chinese adults aged ≥18 years old. The overall follow-up rate of the four cohorts was 93.4% until the recent follow-up survey that ended in 2015. The average of satellite-based PM2.5 concentrations during 2000–2015 at 1-km spatial resolution was assigned to each participant according to individual residence addresses. Based on the pooled analysis of individual data from the four cohorts, a Cox proportional hazards model was used to estimate the hazard ratio (HR) and corresponding 95% confidence intervals (95% CIs) for the association of PM2.5 exposure with mortality after multivariate adjustment. A total of 116,821 participants were eligible in the final analysis. During a mean of 7.7 years of follow-up, 6,395 non-accidental deaths and 2,507 cardio-metabolic deaths occurred. The mean of PM2.5 concentration was 64.9 μg/m3 ranging from 31.2 μg/m3 to 97.0 μg/m3. For each 10 μg/m3 increment in PM2.5, the HR was 1.11 (95% CI: 1.08–1.14) for non-accidental mortality and 1.22 (95% CI: 1.16–1.27) for cardio-metabolic mortality. In addition, a weak exponential curve for the concentration-response association between mortality and PM2.5 was observed among Chinese adults. Our study provided important evidence of the long-term effects of PM2.5 exposure on deaths among Chinese adults. The findings expand our knowledge on concentration-response relationship in high-exposure environments, which is essential to address the urgent challenge of reducing the disease burden attributable to PM2.5 exposure in rapidly industrializing countries such as China.